Delay discounting, but not disinhibition or inattention, partially mediates the effects of neuroticism on disordered eating in adolescents. (August 2015) - Thamotharan, Sneha; Hubbard, Meagan; Fields, Sherecce
Abstract: Adolescence represents an integral developmental period for the prevention and intervention of disordered eating. Individuals with high levels of neuroticism have been shown to respond with greater impulsivity and use of disordered eating as a coping mechanism. However, the exact mechanism through which neuroticism and impulsivity affect disordered eating remains unknown. To understand the effects of personality and impulsivity on disordered eating in adolescence, the present study aimed to investigate whether impulsivity mediated the relationship between neuroticism and disordered eating. Adolescents ( N  = 40) between the ages of 13 and 19 ( M age  = 18.25 years; S.D.  = 1.30) were queried on eating attitudes and personality, as well as completed behavioral tasks assessing impulsivity (delay discounting, disinhibition and inattention). Mediation analyses revealed that neuroticism was significantly associated with patterns of disordered eating, but delay discounting, and not disinhibition and inattention, appeared to mediate the relationship between neuroticism and disordered eating. These results should guide prospective research exploring the relations between neurotic and impulsive behavior, particularly delay discounting on disordered eating, which will assist in future treatment efforts targeting the development of maladaptive eating behaviors. Highlights: Neuroticism was associated with delay discounting. However, neuroticism was not associated with disinhibition or inattention. Delay discounting mediated the relationship between neuroticism and eating concern. For all other domains, except dietary constraint, a partial mediation was found. Neuroticism was not associated with dietary restraint.